2017
DOI: 10.5812/ircmj.59999
|View full text |Cite
|
Sign up to set email alerts
|

Eight-Milligram Single Dose of Buprenorphine as an Expeditious Treatment for Severe Suicidal Ideation: A Case Report

Abstract: Introduction: Buprenorphine is used to treat opioid use disorder and pain syndromes. This drug may be a suitable treatment choice for refractory depression, anxiety, self-injurious behaviors, and suicidal ideation. However, it has a significant abuse potential, which limits its use in suicidal patients with a history of substance abuse. Case Report: In this report, we present a case of chronic suicidal ideation due to substance-induced depressive disorder in a 25-yearold man from Noorabad, Fars, Iran. The pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Regarding the efficacy of BUP on suicidal ideation, in addition to the Striebel report, two other studies were added—one randomized, double-blind, and placebo-controlled clinical trial [ 51 ], and one case report [ 52 ]—for a total of 90 patients having heterogeneous diagnoses (i.e., Borderline Personality Disorder, Major Depressive Disorder, Adjustment Disorders, Eating Disorders, Post-Traumatic Stress Disorder, Substance-Induced Depressive Disorder), but all with clinically significant suicidal ideation. Only one clinical case study about NSSI behavior was found [ 53 ]: it included 6 patients with self-injury behavior who were treated with BUP.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regarding the efficacy of BUP on suicidal ideation, in addition to the Striebel report, two other studies were added—one randomized, double-blind, and placebo-controlled clinical trial [ 51 ], and one case report [ 52 ]—for a total of 90 patients having heterogeneous diagnoses (i.e., Borderline Personality Disorder, Major Depressive Disorder, Adjustment Disorders, Eating Disorders, Post-Traumatic Stress Disorder, Substance-Induced Depressive Disorder), but all with clinically significant suicidal ideation. Only one clinical case study about NSSI behavior was found [ 53 ]: it included 6 patients with self-injury behavior who were treated with BUP.…”
Section: Resultsmentioning
confidence: 99%
“…Three case-reports were included in this review: the studies of Striebel and Kalapatapu [ 47 ], Ahmadi et al [ 52 ], and Norelli et al [ 53 ]. Striebel and Kalapatapu [ 47 ] described the case of a 61-year old women affected by chronic-opiate dependent back pain and depression who was treated with 16 mg/4 mg of BUP/naloxone daily.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations